2019
DOI: 10.2147/cia.s211328
|View full text |Cite
|
Sign up to set email alerts
|

<p>Short-term changes of blood pressure and aortic stiffness in older patients after transcatheter aortic valve implantation</p>

Abstract: Background Both aortic valve stenosis and aortic stiffness are moderators of arterio ventricular coupling and independent predictors of cardiovascular morbidity and mortality. Studies on the effect of transcatheter aortic valve implantation (TAVI) on aortic functional properties are limited. We performed a study to investigate the possible short-term changes in aortic stiffness and other aortic functional properties after TAVI in older patients. Methods TAVI Care&Cure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… Nemes et al 2007 10 12 SAVR, 58% male, mean age 65 ↓SBP 21, 180 and 365 ASi Gradual decreased ASi with time Vavuranakis et al 2012 11 30 TAVI, 47% male, mean age 80 ↑ MAP ⇔ SBP 7–8 ASi No significant Δstiffness nor aortic distensibility Vizzardi et al 2014 12 15 TAVI, 40% male, mean age 83 180 and 365 ASi Sustained decreased stiffness after 12 months and increased distensibility Cantürk et al 2017 14 38 SAVR, 78% male, mean age 59 90 PWV (MOG) Baseline PWV was associated with MPG and AVA. Goudzwaard et al 2019 15 40 TAVI, 58% male, mean age 80 1 PWV and AIx with MOG ΔPWV was inversely correlated with baseline PWV Yotti et al 2015 18 23 TAVI, 63% male, mean age 79 ↑ SBP, DBP, MAP 0 Invasive AIx ↑ Vascular load after TAVI Pagolatou et al 2020 19 33 TAVI, 49% male, mean age 84 ↑ aortic BP ↓ AIx 1 Invasive AIx Müller et al 2018 20 50 TAVI,...…”
Section: Methods To Determine Arterial Stiffness In Aortic Valve Sten...mentioning
confidence: 99%
See 1 more Smart Citation
“… Nemes et al 2007 10 12 SAVR, 58% male, mean age 65 ↓SBP 21, 180 and 365 ASi Gradual decreased ASi with time Vavuranakis et al 2012 11 30 TAVI, 47% male, mean age 80 ↑ MAP ⇔ SBP 7–8 ASi No significant Δstiffness nor aortic distensibility Vizzardi et al 2014 12 15 TAVI, 40% male, mean age 83 180 and 365 ASi Sustained decreased stiffness after 12 months and increased distensibility Cantürk et al 2017 14 38 SAVR, 78% male, mean age 59 90 PWV (MOG) Baseline PWV was associated with MPG and AVA. Goudzwaard et al 2019 15 40 TAVI, 58% male, mean age 80 1 PWV and AIx with MOG ΔPWV was inversely correlated with baseline PWV Yotti et al 2015 18 23 TAVI, 63% male, mean age 79 ↑ SBP, DBP, MAP 0 Invasive AIx ↑ Vascular load after TAVI Pagolatou et al 2020 19 33 TAVI, 49% male, mean age 84 ↑ aortic BP ↓ AIx 1 Invasive AIx Müller et al 2018 20 50 TAVI,...…”
Section: Methods To Determine Arterial Stiffness In Aortic Valve Sten...mentioning
confidence: 99%
“…Two studies used this method of which one noted decreased oPWV 1 day after TAVI and another unchanged oPWV 90 days after SAVR. 14 , 15 However, concerns have been raised based on a study showing that 99.1% of the variation in oPWV was explained by age and systolic blood pressure. 16 Also, a considerable discrepancy between oPWV and cfPWV was observed in a Marfan cohort 17 indicating that oPWV may need validation in specific populations.…”
Section: Methods To Determine Arterial Stiffness In Aortic Valve Sten...mentioning
confidence: 99%
“…As for those who experienced a reduction in PWV, this could be attributed to the impressive reduction of approximately 8.5 mmHg in MBP that was observed as well [24]. Also, results from the TAVI Care&Cure study in the Netherlands showed a reduction in aortic PWV 24h post-TAVI as assessed by Mobil-O-Graph, a finding in all probability driven principally by blood pressure reduction too [47].…”
Section: Aortic Stiffnessmentioning
confidence: 83%
“…In accordance with these acute findings, but also providing long-term results, we recently showed in a cohort of 90 patients undergoing TAVI that the arterial system exhibits an increase of stiffness as assessed by cfPWV and brachial-ankle PWV (baPWV) in response to the acute relief of the obstruction, which is retained in the long term after approximately 1 year of follow-up [35]. However, there are a few, smaller studies indicating no effect or even a decrease in stiffness after intervention [24,47]. These findings must be interpreted with caution; issues on sample size, as well as pressure dependency, might explain the discrepancy.…”
Section: Aortic Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation